Minimally invasive lithium disilicate ceramic veneers fabricated using chairside CAD/CAM: a clinical report - Schmitter, Marc; Seydler, Bodo (The journal of prosthetic dentistry, 2012)
This clinical report describes the use of modern CAD/CAM technology combined with a conventional impression technique to treat a malformed tooth with ceramic veneer in a single appointment. A thin veneer (0.4 mm) made of lithium disilicate ceramic was used to correct the shape of the malformed tooth with a minimally invasive preparation using a chairside CAD/CAM system. Thus the treatment can be performed during one appointment. To facilitate the CAD/CAM process and fabrication of the veneer, a scanable model fabricated on a modified gypsum definitive cast was used. The malformed tooth was corrected on the cast by use of a composite resin and an impression was then made. This trimmed impression was used intraorally during the scanning process to facilitate fabrication of the veneer.